Taxonomic evaluation of a new piscean trematode from freshwater fish Mastacembelus armatus of Maharashtra State, India - Dhole, Jaywant; Kadam, Karmveer; Chavan, Ramrao (Journal of Experimental Sciences, 2013)
The present investigation deals with the taxonomic evaluation of new species of the Piscean trematode of the genus Isoparorchis from freshwater fish Mastacembelus armatus of Maharashtra state provided new data on their morphology. The new species Isoparorchis maharashtrensis Sp. Nov. is comes closer to all the known species of the genus Isoparorchis in general topography of organ but differs due to shape of the body and morphology of internal organs.